Management of Arthrofibrosis of the Knee after an Arthroscopic Meniscectomy with Paralytic Shellfish Poisoning Toxin. Case Report. - Jaime, Hinzpeter; Alvaro, Zamorano; Maximiliano, Barahona; Germán, Möller; Joaquín, Espinoza; Miguel, del Campo; Robin, Piron; Joaquín, M. Sepúlveda; Tamara, Bustamante; Nestor, Lagos (International Physiology Journal, 2018)
Objective: The purpose of this study is to evaluate the use of paralytic shellfish poisoning toxin in a patient with arthrofibrosis of the knee. Arthrofibrosis is a common complication of knee surgery that tends to manifest itself as a limitation of the musculoskeletal ranges. Paralytic shellfish poisoning toxin has been proposed as an alternative treatment for painful musculoskeletal pathologies. Subjects: Use of paralytic shellfish poisoning toxin in arthroscopic menisectomy. Case report. Methods: Three doses of paralytic shellfish poisoning toxin were administered in an intra-articular manner on different days. Functionality, musculoskeletal ranges, pain at rest and pain during motion were evaluated. Results: The current alternatives for management of arthrofibrosis include the use of oral steroids, physiotherapy, mobilization under anesthesia and the liberation of arthroscopic debris. This case is the first report of the use of paralytic shellfish poisoning toxin. The adverse effects the patient presented coincided with those described in the literature but without the presence of severe reactions. Improvement in functional tests, progress in musculoskeletal ranges and a decrease in the level of pain were achieved. Adverse effects included parenthesia and a feeling of weightlessness.
Keywords: Paralytic Shellfish Poisoning Toxin (Neosaxitoxina); Arthroscopic meniscectomy; Meniscectomy; Mobilization under anesthesia (MUA).